Development of in Vitro Propagation Techniques for Endospermum Malaccense M.A and Shorea Parvifolia Dyer - Mohd Yusoff, Aziah (2003)
Endospermum malaccense M .A and Shorea parvifolia Dyer are two commercially important timber species identified as potential plantation species. The procurement and storage of their seeds are difficult and is a major hindrance to plantation establishment. Development of micropropagation techniques is being pursued to provide an alternative in planting stock production. Micropropagation of E. malaccense was achieved through in vitro production of plants through axillary shoots development from nodal segment explants of an elite tree. The explants were initially washed in 10 changes of sterile distilled water, followed by 5 changes of 0.05% (v/v) Tween 20 solution for 10 minutes each . This was then followed by rinsing in 10 changes of sterile distilled water and subsequently sterilised in a solution comprising 60 % (v/v) Clorox and 0.05% v/v Tween 20 for 10 minutes. After which they were rinsed 10 times in 300ml sterile distilled water and finally immersed in 70% (v/v) ethanol for 1 minute. Shoots were induced on the nodal segment explants in MS basal salts supplemented with 22.2 x 10-6 M or 44.4 X 10-6 M. For shoot multiplication, the best medium is MS supplemented with 44.4 x 10-6 M BAP and solidified with a mixture of 1.7 g Gelrite and 4g Bacto agar per liter. In vivo rooting with Seradix 3 was more suitable for in vitro produced shoots of E. maiaeeense, compared with an in vitro rooting technique.